Synergistic anticancer potential of biogenic nanoparticles and cryptomeridiol from Sphaeranthus indicus: targeting gastric cancer through apoptosis and cell cycle arrest - Zhao, Pan; Wang, Jigang; Zou, Chang (Frontiers in Pharmacology, 2025)
BackgroundS. indicus has demonstrated promising therapeutic potential due to its bioactive compounds. This study investigated the cytotoxic and pro-apoptotic effects of Sphaeranthus indicus extract, its active fraction, and biosynthesized silver nanoparticles (AgNPs) on human gastric cancer (HGT-1) cells.MethodsThe plant was collected and subjected to Soxhlet extraction using ethanol, followed by sequential solvent partitioning and silica gel column chromatography to isolate bioactive fractions. Green synthesis of AgNPs was conducted using S. indicus extract. Structural characterization was conducted via UV- spectroscopy, FTIR, XRD, and FESEM. Cytotoxicity was assessed using MTT and CCK-8 assays, while apoptosis induction was evaluated through qPCR and Western blot analysis of key apoptotic markers.ResultsThe ethanolic extract exhibited moderate cytotoxicity against HGT-1 cells, whereas biosynthesized AgNPs demonstrated enhanced anticancer activity with reduced toxicity to normal hepatocytes. The active fraction, identified as cryptomeridiol, showed the highest selectivity and potency against cancer cells. qPCR revealed significant upregulation of p21 and downregulation of CDK2, suggesting cell cycle arrest. Western blot analysis confirmed increased expression of caspase-3 and caspase-9 and a reduction in XIAP, indicating apoptosis activation.ConclusionThis study underscores the potential of S. indicus bioactive compounds and AgNPs as therapeutic agents, particularly against gastric cancer. The findings provide a basis for further exploration into their mechanism of action and broader pharmacological applications. Keywords: S. indicus, Bioactive compounds, Silver nanoparticles (AgNPs), Gastric cancer-HGT-1, Apoptosis.